Formulation of 1% α-mangostin in orabase gel induces apoptosis in oral squamous cell carcinoma - Wipawee Nittayananta; Teerapol Srichana; Jureeporn Chuerduangphui; Ekarat Hitakomate; Kesinee Netsomboon (BMC, 2024)
Abstract Background Plant-derived compounds have chemopreventive properties to be used as alternative medicine. Pericarp of Mangosteen (Garcinia mangostana Linn.), a tropical fruit in Southeast Asia contains a phytochemical α-mangostin (α-MG) that demonstrates potent anticancer effects against various types of cancer. α-MG has been reported to be the most effective agent in human cancer cell lines. The objectives of this study were to develop oral gel formulations containing α-MG and determine their (1) anticancer activity, (2) anti-HPV-16 and antimicrobial activities, (3) nitric oxide (NO) inhibitory activity, and (4) wound healing effect. Methods Formulations of oral gel containing α-MG were developed. Anticancer activity on SCC-25 was assessed. Apoptotic induction was determined using flow cytometry technique. Antiviral activity against HPV-16 pseudovirus and antimicrobial activity against S. mutans, P. gingivalis and C. albicans were investigated. NO inhibition was carried out. Fibroblast cell migration was determined by in vitro scratch assay. Results The formulation of 1% α-MG in orabase gel demonstrated anticancer activity by promoting apoptosis in SCC-25. The induction of apoptotic activity was dose dependent with pronounced effect in late apoptosis. The formulation appeared to reduce cell viability of oral keratinocytes (OKC). At CC50 it showed an inhibition against HPV-16 pseudovirus infection. The formulation had no antimicrobial activity against S. mutans, P. gingivalis and C. albicans. No significant NO inhibitory activity and wound healing effects were found. Conclusions 1% α-MG in orabase gel exhibited anticancer activity by inducing apoptosis although low level of cytotoxicity observed in OKC was present. The appropriate carrier for novel nano-particles targeting cancer cells should be further investigated.